TINJAUAN FIQIH MUAMALAH PADA PRAKTIK SEWA MENYEWA LAHAN TAMBAK SISTEM SETORAN DI DESA TAJUNG WIDORO, BUNGAH ,GRESIK - Dinna Emilia Nafa’a; M. Shaiful Umam; Dwi Afrianti (STKIP Subang, 2026)
Fishpond land leasing through a deposit payment system has become a long-standing practice in Tajung Widoro Village, Bungah District, Gresik Regency. The practice is based on verbal agreements and mutual trust, raising questions regarding its compliance with the principles of fiqh muamalah. This study aims to analyze the implementation of the deposit payment system in fishpond land leasing and evaluate its conformity with the principles of ijarah and 'urf. This research employed a qualitative approach with a descriptive phenomenological design. Data were collected through observation, in-depth interviews, and documentation involving landowners, tenants, village officials, and religious leaders. The data were analyzed using data reduction, data display, and conclusion drawing, while validity was ensured through triangulation. The findings show that the leasing practice generally fulfills the pillars and conditions of an ijarah contract, including competent contracting parties, a clearly identified leased object, agreed benefits, and rental payment (ujrah). However, unclear payment schedules and delayed installments may create minor uncertainty (gharar yasir). These issues have not resulted in significant disputes because the practice is widely accepted as 'urf shahih. Therefore, the deposit payment system is considered valid according to fiqh muamalah, provided that contractual clarity, justice, mutual consent, and good faith are maintained.